Development of Graphic User Interface for A Comprehensive Analysis of Dissolved Gas in Transformer Oil - Ahmad Lotfi, Muhammad Nazmi; Mohd Yousof, Mohd Fairouz (Evolution in Electrical and Electronic Engineering, 2022)
Generally, the site location does not have additional transformer backup in case of maintenance or breakdown. In this study, Dissolved Gas Analysis (DGA) was used to measure the condition of oil-immersed by measuring the gas in parts per million (ppm) according to the IEC 60599 and IEEE C 57-104TM standards. It determines whether a transformer in service is ageing normally and in good condition, or if it is developing faults such as hot spots, arcing, overheating, or partial discharge. Therefore, App Designer MATLAB was used in developing a Graphical User Interface (GUI) for DGA interpretation in transformer oil with the suggested electrical test. The aims of this research are to analyze the DGA result based on Duval Triangle (DT) and Duval Pentagon (DP) analyses as well as develop a table of transformer maintenance guidelines based on the DGA's fault diagnosis. The DGA interpretation by DT and DP results showed that stray gassing oil is faulty due to the high production of gases such as hydrogen, methane, and ethane in oils. Therefore, according to maintenance guidelines, the stray gassing test (on the oil samples) must be taken immediately. To sum up, in this paper, the development of the GUI for DT and DP based on DGA interpretation provides the best results of maintenance and diagnostic techniques to determine the condition of transformers and electrical test action to be taken.